Răspuns :
a) x+7=3, x=3-7 ⇒x=-4
b) 6-x=15, x=6-15 ⇒ x= -9
c) -2-x=-5, -x=-5+2, -x=-3 ⇒x=3
d) 16-x=-4, -x=-16-4, -x=-20 ⇒x=20
e) 11-x=14, -x=14-11, -x=3 ⇒x=-3
f) -x+4=-9, -x=-9-4, -x=-13 ⇒x=13
a) x+7=3=x=7-3=x=4
b) 6-x=15=-x=15+6=-x=21/*(-1)=x=-21
c) -2-x=-5=-x=-5+2=-x=-3/*(-1)=x=3
d) 16-x=-4=-x=16+4=-x=20/*(-1)=x=-20
e) 11-x=14=-x=14-11=-x=3/*(-1)=x=-3
f) -x+4=-9=-x=-9-4=-x=-13/*(-1)=x=13
Sper ca te am ajutat!!!!!!!!
b) 6-x=15=-x=15+6=-x=21/*(-1)=x=-21
c) -2-x=-5=-x=-5+2=-x=-3/*(-1)=x=3
d) 16-x=-4=-x=16+4=-x=20/*(-1)=x=-20
e) 11-x=14=-x=14-11=-x=3/*(-1)=x=-3
f) -x+4=-9=-x=-9-4=-x=-13/*(-1)=x=13
Sper ca te am ajutat!!!!!!!!